Effects of prenatal polycyclic aromatic hydrocarbons and childhood material hardship on reading achievement in school-age children: A preliminary study - Greenwood, Paige B.; Cohen, Jacob W.; Liu, Ran; Hoepner, Lori; Rauh, Virginia; Herbstman, Julie; Pagliaccio, David; Margolis, Amy E. (Frontiers in Psychology, 2023)
Background: Children from socioeconomically disadvantaged backgrounds are at elevated risk for reading problems. They are also likely to live in neighborhoods with high levels of air pollution and to experience material hardship. Despite these risk factors, the links between prenatal chemical exposures, socioeconomic adversities, and reading problems in youth from disadvantaged backgrounds remain understudied. Here we examine associations between prenatal exposure to polycyclic aromatic hydrocarbons (PAH), a common air pollutant, and reading skills, and determine if this relationship is exacerbated by material hardship among Black and/or Latinx children who have been followed as part of a longitudinal urban birth cohort. Methods: Mothers and their children, who were participants in a prospective birth cohort followed by the Columbia Center for Children’s Environmental Health, were recruited for the current study. Personal prenatal PAH exposure was measured during the third-trimester of pregnancy using a personal air monitoring backpack. Mothers reported their level of material hardship when their child was age 5 and children completed measures of pseudoword and word reading (Woodcock Johnson III Tests of Achievement (WJ-III) Basic Reading Index) at age 7. We used multiple linear regression to examine the effects of the interaction between prenatal PAH and material hardship on Basic Reading Index, controlling for ethnicity/race, sex, birthweight, presence of a smoker in the home (prenatal), and maternal education (prenatal) (N=53). Results: A prenatal PAH × material hardship interaction significantly associated with WJ-III Basic Reading Index scores at age 7 (β=-.347, t(44)=-2.197, p=.033). Exploratory analyses suggested that this effect was driven by untimed pseudoword decoding (WJ-III Word Attack: β=-.391, t(44)=-2.550, p=.014). Conclusions: Environmental chemical exposures can be particularly toxic during the prenatal period when the fetal brain undergoes rapid development, making it uniquely vulnerable to chemical perturbations. These data highlight the interactive effects of environmental neurotoxicants and unmet basic needs on children’s acquisition of reading skill, specifically phonemic processing. Such findings identify potentially modifiable environmental risk factors implicated in reading problems in children from economically disadvantaged backgrounds.